الجريدة الرسمية العدد 41 مكرر (ج) - رئيس مجلس الوزراء (المطابع الاميرية, 2025)
قرارات رئيس مجلس الوزراء : قرار رقم 3424 لسنة 2024 -- قرار رقم 3451 لسنة 2024 -- قرار رقم 3453 لسنة 2024 -- قرار رقم 3454 لسنة 2024 -- قرار رقم 3458 لسنة 2024 -- قرار رقم 3459 لسنة 2024